ANALISA HUKUM ATAS KEPEMILIKAN SAH BAGI HAK CIPTA LAGU ATAU MUSIK (PERATURAN NOMOR 56 TAHUN 2021): Legal Analysis of Legal Ownership of Song or Music Copyrights (Regulation Number 56 of 2021) - Kalisa, Eka Aslihatin S Putri (Fakultas Hukum, Universitas Trisakti, 2024)
The uncertainty of legal regulations concerning the economic entitlements of songwriters or musicians and related rights in asserting royalties can arise due to the failure to register the data of songwriters or musicians along with their related rights in the Song and Music Information System (SILM) and the Directorate General of Intellectual Property (DJKI) database. In an attempt to offer legal safeguard for copyright or related rights in the music industry that are not registered in SILM, this study seeks to examine the legal consequences of such situations and the patterns of dispute resolution. Through observation of the research object and the degree of its application in practice, empirical sociology is the applied method used to evaluate the efficiency of legal tools in complying with prevailing regulations. Findings indicate that in cases of music compositions or songs not included in SILM, users are willing to pay royalties in exchange for not releasing new recordings, and that to achieve mutually beneficial agreements, conflict resolution procedures typically require mediation through PPNS before resorting to litigation.